Impacto de la calidad institucional en el crecimiento económico de América del Sur, período 2002 – 2021. - Bravo Maya, Marlon Gustavo (2023)
The aim of this study is to determine the impact of institutional quality on the economic growth of South America for the period 2002 - 2021. The econometric analysis is conducted through the estimation of a panel data model that links the institutional quality index with per capita GDP and other control variables such as human capital, physical capital, and economic freedom. The results obtained indicate that the institutional quality index has a positive and significant impact on economic growth, highlighting the importance of corruption control for the development of an inclusive economic-social structure that promotes innovation, economic growth, and social welfare.